HUBUNGAN KREATIVITAS DENGAN HASIL BELAJAR SISWA DESAIN KOMUNIKASI VISUAL SMK NEGERI 4 PADANG - Firmansyah, Dr. Yahya, M. Pd, Drs. Mediagus (Universitas Negeri Padang, 2013)
The purpose of this research is to know if there any relationship between students „creativity to students‟ achievement in Visual Communication Design program and to know the significance of its relationship. This is correlation research. The prior data was got from questionnaire that had been indicated students‟ creativity. The secondary data was got from the students‟ achievement in sample group. The data was analyzed by using SPSS version 18. The finding shown that there is significance relationship in the number of 0,466 and the students‟ creativity gave positive contribution in the number of 20,3% to students‟ achievement in grade XI of Visual Communication Design program. Kata kunci: Kreativitas, Hasil Belajar